Cytomegalovirus colitis and oesophageal ulceration in the context of AIDS: clinical manifestations and preliminary report of treatment with Foscarnet (phosphonoformate). Issue 4 (April 1987) - Weber, J N; Thom, S; Barrison, I; Unwin, R; Forster, S; Jeffries, D J; Boylston, A; Pinching, A J
Abstract : Three patients with biopsy diagnosed invasive cytomegalovirus infection of the colon have been seen in the context of the acquired immune deficiency syndrome (AIDS). Cytomegalovirus colitis presented with fever, abdominal distention, bloody diarrhoea and weight loss. Plain abdominal radiographs showed generalised large bowel dilatation in one patient. Cytomegalovirus infection was shown histologically, but the virus could not be cultured from the stool; no other gastrointestinal pathogens could be demonstrated. The patients were treated with a 14 day continuous infusion of Foscarnet 0.08 mg/kg/min (phosphonoformate, Astra Pharmaceuticals). One patient showed a partial response to therapy, but the cytomegalovirus colitis relapsed; the second patient had a symptomatic response only and the third patient died of non-cytomegalovirus opportunist infection while on treatment. Two other patients with biopsy proven cytomegalovirus ulceration of the oesophagus were seen, presenting with dysphagia, fever and weight loss. Invasive infection of the gastrointestinal tract with cytomegalovirus is now a major clinical problem in AIDS. Treatment with Foscarnet may be initially effective, but does not eliminate cytomegalovirus infection.